Acute CoVID-19-associated bilateral neuropathy of the abducens nerve in a child - V. B. Voitenkov; E. Yu. Gorelik; N. V. Scripchenko; N. V. Marchenko; A. V. Klimkin; M. A. Bedova (Журнал инфектологии, 2021)
We have presented the first description of acute bilateral neuropathy of the abducens nerve associated with COVID-19 in a child.A boy aged 2 years 2 months acutely developed bilateral convergent strabismus, the next day fatigue, drowsiness, and a single vomiting not associated with food intake, were joined. A differential diagnosis was performed between brainstem encephalitis, other organic (non-inflammatory) lesions of the brain stem, and idiopathic bilateral neuropathy of the abducens nerves. According to laboratory data, mild lymphocytosis, mild eosinophilia were detected, according to polymerase chain reaction DNA of the herpes virus type 1/2, cytomegalovirus, herpes virus type 6, Epstein-Barr, tick-borne encephalitis, borrelia, anaplasma, RNA ehrlichia were not detected. IgM and IgG to tick-borne encephalitis were not detected. Neurophysiological and neuroimaging examinations did not reveal any pathology. On the 6th day of the disease, SARS-CoV-2 RNA was detected by polymerase chain reaction of the nasopharynx and oropharynx discharge. The final diagnosis was formulated. — bilateral neuropathy of the abducens nerves. Bilateral convergent paralytic strabismus. Concomitant diagnosis: new coronavirus infection, subclini-cal form (positive by polymerase chain reaction in the discharge from the throat and nose of the 2019-nCoV coronavirus (SARS-CoV-2) RNA). Decrease in the severity of strabismus was noted over time against the background of the therapy.Clinicians dealing with the COVID-19 should also pay attention to its ophthalmological manifestations and take into account that it can debut with them, as was in our case.